2020
DOI: 10.1055/a-1211-6325
|View full text |Cite
|
Sign up to set email alerts
|

Clary Sage Essential Oil and Its Effect on Human Mood and Pulse Rate: An in vivo Pilot Study

Abstract: Clary sage (Salvia sclarea) is a xerophytic biennial plant typical for the Mediterranean region. It is cultivated for its essential oil, which is widely used in the flavor and fragrance industry as well as in aromatherapy for its relaxing and immunomodulatory effect. In this pilot investigation, clary sage essential oil was analyzed by GC-MS as well as GC-FID and examined regarding its effects on pulse, blood pressure and mood in healthy human female and male subjects. Analysis of the used CSEO identified lina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Biomarcadores aumentados na ansiedade, como nível de carboidrato, por exemplo, sofreram redução após 10 dias de inalação [24]. Foi constatada em outro estudo a redução da pulsação após inalação do óleo essencial de Sálvia esclaréia em mulheres, apesar de não terem sido observadas mudanças na pressão arterial nem no humor (com base nos questionários aplicados antes e após a intervenção) [10]. Com base nesses achados, percebe-se que o óleo essencial de Sálvia esclaréia pode ser útil para atenuar sintomas da ansiedade, o que pode auxiliar pessoas passando por momentos de ansiedade diversos, como durante o parto ou no pós-parto, durante o climatério, entre outros momentos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Biomarcadores aumentados na ansiedade, como nível de carboidrato, por exemplo, sofreram redução após 10 dias de inalação [24]. Foi constatada em outro estudo a redução da pulsação após inalação do óleo essencial de Sálvia esclaréia em mulheres, apesar de não terem sido observadas mudanças na pressão arterial nem no humor (com base nos questionários aplicados antes e após a intervenção) [10]. Com base nesses achados, percebe-se que o óleo essencial de Sálvia esclaréia pode ser útil para atenuar sintomas da ansiedade, o que pode auxiliar pessoas passando por momentos de ansiedade diversos, como durante o parto ou no pós-parto, durante o climatério, entre outros momentos.…”
Section: Discussionunclassified
“…Título/Autoria/Ano/País Resultados principais Tipo de estudo Clary sage essential oil and its effect on human mood and pulse rate: an in vivo pilot study. [10] 2020. Áustria.…”
Section: Quadro 2 -Dados Dos Artigos Incluídos Na Revisão São Paulo S...unclassified
“…Effects of essential oil from S. sclarea on pulse, blood pressure and mood were analyzed on healthy female and male humans (Mitic et al, 2020). The pulse rate decreased more significantly in women than in men.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, according to previous research, lavender has stress-relieving and pain-control impacts and may help prevent depression (Chioca et al, 2013;Nasiri et al, 2016;Zamanifar et al, 2020). Another recognized relaxing smell is Salvia Sclarea or clary sage, which studies indicated has an impact on relaxation by alleviating pain and blood pressure (Mitic et al, 2020;Yang et al, 2014;You et al, 2011).…”
Section: Olfactionmentioning
confidence: 99%